Long-term computed tomographic changes in cystic fibrosis patients treated with ivacaftor. Issue 1 (26th May 2016) - Chassagnon, Guillaume; Hubert, Dominique; Fajac, Isabelle; Burgel, Pierre-Régis; Revel, Marie-Pierre
Cystic fibrosis (CF) patients with gating mutations in the gene coding for the CF transmembrane conductance regulator (CFTR) protein have been the first to benefit from CFTR-targeted therapies since the approval of ivacaftor in 2012 by the Food and Drug Administration and the European Medicines Agency. Ivacaftor is a potentiator that increases chloride transport through the defective CFTR protein [1, 2]. In phase III clinical trials, ivacaftor significantly improved lung function and clinical status in patients with a G551D mutation aged ≥6 years [3, 4]. In the two studies conducted in adults and children, the forced expiratory volume in 1 s (FEV1 ) showed a 10.4% predicted and 12.5% pred point increase from baseline after 24 weeks of treatment, as compared to a 0.1 and 0.2% pred point decrease in the control group. Clinical efficacy of ivacaftor was also shown in patients with other gating mutations of the CFTR gene, with a 7.5% pred point increase in FEV1 after 8 weeks of treatment [5]. In all these phase III studies, the primary endpoint was the change in FEV1 and secondary endpoints were other clinical and functional parameters, such as change in weight, respiratory exacerbation rate, health status, and sweat-chloride concentration. Imaging was never listed as an endpoint. Data on computed tomography (CT) changes upon ivacaftor treatment are scarce [6–8] and long-term changes remain unknown. The aim of this study was to assess short- and long-term CT changes in adult CF patients treated with ivacaftor. In CF patients treated with ivacaftor, improvement of CT abnormalities remains stable on long-term follow-up http://ow.ly/Zxu2B